Journalistic (re)production of history - Erjavec, Karmen (Šolsko polje, 2009)
The arrest of former Bosnian Serb political and military leader Radovan Karadžić in July 2008 triggered a wide-spread interest within international community and provided the opportunity for the Serbian public and its media to reflect upon the role of Serbia during the 1990s Yugoslav wars. Karadžić was as a president of the self-proclaimed Serbian republic within Bosnia and Herzegovina. He was accused for genocide and crimes against humanity in 1995. On the basis of critical discourse analysis (the analysis of recontextualization and the analysis of representation of social actors), we argue that Television Serbia's journalists, while covering Karadžić's arrest, reproduced a nationalistic discourse by invoking nostalgia for Greater Serbia in ways that concealed any connection between Karadžić specifically, the Serbs in general, and especially the current government with war crimes in Bosnia and Herzegovina. At the same time this discourse celebrated Serbia as a superior nation as it progressed toward inclusion in the European Union.
Keywords: diskurz; kritična analiza diskurza; množični mediji; nacionalizem; Srbija; televizija; zgodovina